Virtual reality-based emotion-to-emotion therapy for post-traumatic stress disorder: Protocol for a randomized controlled trial of efficacy, safety, and cost-effectiveness - Do-Eun Lee; Namju Lee; Nam-Kwen Kim; Joohee Seo; Jaeuk U. Kim; In Chul Jung; Moon Joo Cheong; Hyung Won Kang (PLOS One, 2026)
Background Trauma-focused psychotherapies are recommended first-line treatments for post-traumatic stress disorder (PTSD). Emotion-to-Emotion Therapy (ETE) is a psychotherapy derived from traditional Korean medicine that regulates excessive emotional responses using theoretically opposing emotions. Virtual reality (VR) may support standardized and immersive delivery of the meditation component of ETE. This trial will evaluate the efficacy, safety, and cost-effectiveness of VR-based ETE for PTSD. Methods This multicenter, randomized, waitlist-controlled, assessor-blinded trial will enroll 72 adults with PTSD and allocate them 1:1:1 to VR-based ETE, standard ETE, or a waitlist control group. Both active groups will receive 16 sessions over 8 weeks; waitlist participants will continue usual activities with scheduled monitoring. The primary endpoint is the between-group difference in the week-8 Korean version of the PTSD Checklist for DSM-5 (PCL-5-K) total score, adjusted for the baseline PCL-5-K score and study site. A week-12 follow-up assessment will examine the durability of treatment effects. Secondary outcomes, assessed at baseline and weeks 8 and 12, include the Core Seven-Emotions Inventory–Short Form, Korean Posttraumatic Growth Inventory, Five Facet Mindfulness Questionnaire–Short Form, Patient Health Questionnaire-15, Hospital Anxiety and Depression Scale, Korean Insomnia Severity Index, Hwa-Byung Scale, Clinical Global Impression scales, quantitative electroencephalography, and heart rate variability. Health-related quality of life and cost data will be collected for a within-trial economic evaluation. Discussion This trial will provide preliminary randomized evidence on the efficacy, safety, and cost-effectiveness of standard and VR-based ETE for PTSD, and on whether adding VR to the meditation component of ETE offers clinical value beyond standard ETE. Interpretation will need to consider the modest sample size, the absence of participant blinding, and the use of a waitlist rather than an active control condition. Trial registration Clinical Research Information Service of the Republic of Korea, KCT0007845 . Registered on October 18, 2022.